Model civic learning berbasis kewarganegaraan digital untuk pemberdayaan platform digital komunitas di media sosial - Anugrah Setiawan; Radini (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
The development of digital technology in Indonesia has created new spaces for participation, but has not been matched by adequate digital citizenship literacy. Digital communities, such as the Mosque Cleaning Community (KPM), have substantial social capital but have not yet optimally utilized digital platforms for civic engagement. This community service (PkM) activity aims to implement a digital citizenship-based civic learning model to empower KPM. The PkM implementation method uses a participatory approach adapted from the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The activity stages include: (1) Analysis of partner needs through digital observation and online interviews; (2) Intervention design in the form of workshops and mentoring materials; (3) Development of relevant educational content; (4) Program implementation through online workshops and intensive mentoring in partner social media groups; and (5) Program evaluation using pre-tests and post-tests as well as qualitative observations. The results of the community service show a significant increase in the knowledge, awareness, and digital citizenship skills of KPM members. There has been a transformation in the use of community social media, from being passively informative to being more participatory, critical, and educational. This program successfully increased the community's civic engagement capacity in the digital space. The implications of this activity suggest the adoption of a similar model by policymakers, such as the Indonesian Mosque Council (DMI) and the Education Office, for broader youth development.